Effects of drone pupae excised on the colony productivity, reproductive capacity and swarming - ZHENG Zhi-jiang; WU Gui-sheng; ZHANG Zhong-yin; GUO Dong-sheng (浙江大学学报. 农业与生命科学版, 2000)
The experiments were conducted with Apis mellifera ligustica. The colonies were divided into trial and control group. In the trial group, sealed drone pupae were cut out. In the control group, sealed drone pupae were not cut. The colony productivity, reproductive capacity and swarming were regularly measured during the test. The results showed that there was no significant difference on the royal jelly output, colony reproductive capacity and swarming between the two groups. But the honey output of the control group was 8.4%-10.0% higher than that of the trial group. The results showed that the beekeepers need not cut out the drone pupae during keeping bees.